The Implementation Of Online-Based Project Based Learning During The Covid-19 Pandemic In Malay Arabic Courses Semester V In Indonesian Literatures Jambi University - Warni; Rengki Afria (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to describe the implementation of online-based Project Based Learning in the Arabic-Malay Script Course in Semester V of the Indonesian Literature Study Program, FKIP, Jambi University. The method used is an action research method. Sources of data in the form of stimulus and student responses in learning. The results of the study concluded that the implementation of PJBL in the Malay Arabic Script course had been carried out well. This is evidenced by the students' awareness of the importance of the Malay Arabic script.